Evaluasi Penerapan Sanitasi dan Pengendalian Vector pada Kapal Penumpang di Pelabuhan Parepare - Ahmad Fuad Rabbani; Usman Usman; Nurlinda Nurlinda (Media Literasi Indonesia, 2025)
Ship sanitation is very important because it can prevent and minimize the presence of vectors as the cause of disease transmission. The inspection of ship sanitation is intended to ensure that the ship is free from the threat of disease that has the potential to become an epidemic, to prevent the transmission of infectious diseases, and to create a comfortable and safe atmosphere for passengers. This study aims to determine how the implementation of sanitation and vector control on passenger ships at the Nusantara Port, Parepare City. This type of research is an observational study with a descriptive approach. The sample of this research is 5 passenger ships whose inspection schedule is from June to July 2021. From the results of the study, it was found that there are still many ships that have not implemented proper sanitation according to PMK RI NO. 40 YEAR 2015 Regarding Ship Sanitation Certification, one of the sanitation conditions that greatly affects the presence of vector signs is the aspect of waste management in the kitchen room, passenger bedroom, and toilet. As well as poor air circulation that triggers the presence of vectors. 100% ship sanitation hygiene does not meet the requirements in all aspects, it can cause vector signs, such as mosquitoes, cockroaches and flies. Suggestions for crew and ship managers at the Nusantara Harbor in Parepae City, it is recommended to improve the quality of ship sanitation hygiene, especially on 7 aspects that have not met the requirements by all ships, namely facilities in toilets, food raft rooms, passenger sleeping rooms, food and garbage. This must be done in order to avoid the spread of diseases caused by vectors.